Driver Intention Recognition for Mine Transport Vehicle Based on Cross-Modal Knowledge Distillation - Yizhe Zhang; Yinan Guo; Xiusong You; Lunfeng Guo; Bing Miao; Hao Li (Applied Sciences, 2025)
Driver intention recognition is essential for optimizing driving decisions by dynamically adjusting speed and trajectory to enhance system performance. However, in the underground coal mine environment, traditional vision-based methods face significant limitations in accuracy and adaptability. To effectively improve the accuracy of vision-based driver intention recognition, this study introduces a novel approach leveraging cross-modal knowledge distillation (CMKD) to integrate electroencephalography (EEG) signals with video data to identify driver intentions in coal mining operations. By combining these modalities, the method capitalizes on their complementary strengths to achieve a more comprehensive understanding of driver intent. Experimental analysis across various models evaluates the performance of the proposed CMKD method, which integrates EEG signals with video data. Results reveal a substantial improvement in recognition accuracy over traditional machine vision-based approaches, with a maximum accuracy of 84.38%. This advancement enhances the reliability of driver intention detection and offers more robust support for decision making in automated mine transport systems.